Micro-scale abrasion of WC-based coatings with different abrasive type - Kamdi, Z.; Shipway, P. H.; Voisey, K. T. (Trans Tech Publications, 2013)
Various research programmes have been conducted examining cermet coatings regarding wear, corrosion and the combination of both (erosion-corrosion and abrasion-corrosion). Several methods have been used to deposit cermet coatings, the most common being thermal spraying or hard facing (weld overlaying). In the current work, the micro-scale abrasion of coatings deposited using both high velocity oxy-fuel (HVOF) thermal spraying and weld overlay techniques are compared. The weld-overlayed WC-nickel alloy systems have the carbide particles are typically two orders of magnitude larger than in the sprayed coatings. Micro-scale abrasion tests were performed using silicon carbide, alumina and silica particle slurries with abrasive particle sizes in the range of 2-10 µm in all cases. Wear rates were determined and the wear scars were examined using SEM to elucidate the dominant wear mechanisms. The wear rate is generally observed to decrease with decreasing abrasive hardness from silicon carbide, followed by alumina and silica.